1994
DOI: 10.1161/01.str.25.9.1771
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral autoregulation in orthostatic hypotension. A transcranial Doppler study.

Abstract: Background and Purpose Transcranial Doppler measurements of blood flow velocity permit an assessment of variations in intracraniaJ hemodynamics in response to acute arterial pressure variations. The purpose of this study was to scan healthy volunteers and patients with autonomic failure for differences in cerebral hemodynamic patterns under an acute hypotensive stimulus.Methods We used transcranial Doppler monitoring of blood flow velocity in the middle cerebral artery and noninvasive monitoring of arterial bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…31 Thus, cerebrovascular vasomotor reserve seems to be reduced with only a limited capacity to compensate for changes in BP. Previous studies 32,33 using the reactive hyperemia test have also demonstrated that cerebral circulation passively follows the rise and fall in BP in the supine position in patients with multiple system atrophy and autonomic failure. 33 The possibility of a passive vasodilatation has also been raised based on comparisons between MCA flow velocity and 133 Xe washout measurements of cerebral blood flow in patients with multiple system atrophy and autonomic failure during 45°HUT.…”
Section: Discussionmentioning
confidence: 90%
“…31 Thus, cerebrovascular vasomotor reserve seems to be reduced with only a limited capacity to compensate for changes in BP. Previous studies 32,33 using the reactive hyperemia test have also demonstrated that cerebral circulation passively follows the rise and fall in BP in the supine position in patients with multiple system atrophy and autonomic failure. 33 The possibility of a passive vasodilatation has also been raised based on comparisons between MCA flow velocity and 133 Xe washout measurements of cerebral blood flow in patients with multiple system atrophy and autonomic failure during 45°HUT.…”
Section: Discussionmentioning
confidence: 90%
“…Clinical applications of the thigh cuff technique have included patients with orthostatic hypotension, 10 carotid artery disease, 11 head injury, [12][13][14] and studies of the effects of anesthetic agents on cerebral autoregulation. 15,16 Despite its increasing use in cerebrovascular research, several aspects of the thigh cuff method have not been described.…”
mentioning
confidence: 99%
“…As it has been shown that OH is found in PD patients, it is then also important to ask whether or not cerebral autoregulation (CA) is impaired in PD. This is because in cases of OH, it has been found that CA is not as effective, and this could prove to be dangerous for patients with PD [4].…”
Section: Introductionmentioning
confidence: 99%